2014
DOI: 10.1111/jam.12700
|View full text |Cite
|
Sign up to set email alerts
|

Phages in the global fruit and vegetable industry

Abstract: Summary From recent articles, we have learned that phages can constitute a promising alternative in the food industry to eliminate bacterial pathogens from seedlings in greenhouse and field environments, as well as from fresh‐cut food products. The fruit and vegetable industry requires quite a different approach than the meat or dairy industry. Several factors can inhibit efficacy of phage treatment such as plant watering or washing ready‐to‐eat products (water may dilute therapeutic doses), UV irradiation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 81 publications
0
23
0
1
Order By: Relevance
“…It has been concluded that bacteriophages could reduce the number of pathogens by at least one log or 90% (Zaczek et al, 2015). So, at least for Enterohaemorhagic E. coli, Salmonella Sp, and Listeria monocytogenes , the use of bacteriophages could be useful as one amongst several hurdles to ensure food safety.…”
Section: Abiotic Factors To Be Considered In the Hurdle Approachmentioning
confidence: 99%
“…It has been concluded that bacteriophages could reduce the number of pathogens by at least one log or 90% (Zaczek et al, 2015). So, at least for Enterohaemorhagic E. coli, Salmonella Sp, and Listeria monocytogenes , the use of bacteriophages could be useful as one amongst several hurdles to ensure food safety.…”
Section: Abiotic Factors To Be Considered In the Hurdle Approachmentioning
confidence: 99%
“…The use is limited due to regulatory restrictions, pathogen resistance development, and consumers' demands. 2 Biocontrol of bacterial plant pathogens using bacteriophages (phages) has gained increased attention in agriculture as an alternative treatment, 3,4 and several studies have demonstrated the potential of phages to control fire blight. Phage-treatment significantly reduced the number of viable E. amylovora and symptom development in vitro, 5,6 on immature pear fruit, 7,8 on detached flowers, 8,9 and on apple trees.…”
Section: Introductionmentioning
confidence: 99%
“…Polyvalent phages can be used in search and for creating antimicrobial agents based on bacterial viruses (Sadunishvili, 2013;Żaczek et al, 2015). The isolated phages may be considered as an effective component in the creation of therapeutic phage mixtures (Rene et al, 2008).…”
Section: Resultsmentioning
confidence: 99%